Application of Islamic Religious Education (PAI) Teacher Learning to Deaf Children at Tenggarong 1 State Special School - Nuraini, Vahra; Riadi, Akhmad (STMIK Widya Cipta Dharma, 2024)
One of the most important aspects of improving the quality of life is education and schooling. Education is a process that involves the comprehensive and continuous assessment and guidance of individuals. In psychological literature, children with abnormalities in mental and physical functioning, particularly those with learning difficulties, are referred to as having Learning Disabilities. Children with these disorders experience delays in certain learning abilities. Education at Sekolah Luar Biasa (SLB) Negeri 1 Tenggarong provides opportunities and support for children with special needs, including those who are Deaf. The purpose of this study is to analyze the implementation of Islamic religious education in the teaching and learning process between teachers and students at Sekolah Luar Biasa (SLB) Negeri 1 Tenggarong. This research employs a qualitative approach through observation, interviews, and documentation. Data analysis techniques used include data reduction, data presentation, verification, and conclusion drawing. The results of this study indicate that Islamic religious education (PAI) provided to children with special needs contributes positively to their cognitive, social, and emotional development through contextual and inductive approaches applied effectively and efficiently. However, despite these efforts, some children still face difficulties in understanding the material provided.